Change management & benchmarking analysis : case study of the collective bargaining system in Iceland - María Kristín Guðjónsdóttir 1991- (2017)
The appendices have been removed due to confidentiality. The collective bargaining system is a set of rules and measures to ensure efficient wage formation. One of the direct results of a failed collective bargaining process are industrial actions where the conflict is no longer only a concern for the disputing parties but becomes a public policy concern with economic and social costs. Experience shows that some systems are more efficient in promoting mutual gain and preventing disputes from escalating into major conflicts than others. This thesis explores total of six different collective bargaining and labour dispute management systems in Iceland, Australia, Austria, Germany, the Netherlands and Sweden. The objective is to identify and evaluate best practices through benchmarking analysis that can be used to improve the performance of the collective bargaining process in Iceland. This cannot be done without considering the process of change. Hierarchical relationships, power and bureaucracies are factor that often obstruct change management processes in public organizations. The collective bargaining system in Iceland operates in a dynamic environment where change is a deep-rooted element and thus needs to be able to adapt its direction, structure and capabilities. Conclusions of this benchmarking analysis indicate that all researched collective bargaining and labour dispute management systems are underperforming in terms of dispute prevention and performance management. Keywords: Change management, benchmarking, collective bargaining, labour dispute management. The appendices have been removed due to confidentiality.